Actigraphy, the Alternative Way? - De Weerd, Al W. (Frontiers in Psychiatry, 2014)
The gold standards for measurement of sleep and wake are polysomnography (PSG) and the multiple sleep latency test (MSLT) and will remain so. Actigraphy is cheap, less labor intensive for the sleep laboratory and gives no burden for the patient. Major features of sleep (time in bed, total sleep time, sleep onset latency, wake after sleep onset and naps during the day) are easily quantified. If done over at least five days the results are in a reasonable way comparable to those of PSG. Obviously, actigraphy provides less details of sleep and the way it is disturbed. From the combination of PSG and one week actigraphy, one gets all details of sleep and wake and their fluctuations over time. As “stand alone” technique, actigraphy is indicated in young children, mentally handicapped patients and in the assessment of therapy for sleep disorders. In our opinion assessment of sleep disorders in children should include actigraphy over at least 5-7 24 hour days, if possible combined with one or two nights PSG. As there are no strict rules and normal values for MSLT in children, actigraphy is also helpful as tool for global assessment of hypersomnia in young patients.